2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610755
|View full text |Cite
|
Sign up to set email alerts
|

FES-cycling training in Spinal Cord Injured patients

Abstract: Among the objectives of spinal cord injury (SCI) rehabilitation, (i) prevention of bony, muscular and joint trophism and (ii) limitation of spastic hypertone represent important goals to be achieved. The aim of this study is to use functional electrical stimulation (FES) to activate pedaling on cycle-ergometer and analyse effects of this technique for a rehabilitation training in SCI persons. Five spinal cord injured subjects were recruited and underwent a two months FES-cycling training. Our results show an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Furthermore, ES appears to be well tolerated and has been studied in regard to its effects on preventing skeletal muscle atrophy as well as improving skeletal muscle volume and function. Although the effects of ES on muscle volume in patients with SCI remains unclear [7][8][9], a recent meta-analysis has suggested that ES of the abdominal muscles is an effective technique for improving respiratory function in such patients [10]. The only other meta-analysis found describes the possible effects of ES on increasing bone mineral density below the level of the injury in patients with chronic SCI [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ES appears to be well tolerated and has been studied in regard to its effects on preventing skeletal muscle atrophy as well as improving skeletal muscle volume and function. Although the effects of ES on muscle volume in patients with SCI remains unclear [7][8][9], a recent meta-analysis has suggested that ES of the abdominal muscles is an effective technique for improving respiratory function in such patients [10]. The only other meta-analysis found describes the possible effects of ES on increasing bone mineral density below the level of the injury in patients with chronic SCI [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have presented evidence of health and fitness benefits emerging from cycling assisted by functional electrical stimulation (FES Cycling) for subjects with spinal cord injury (SCI) . Among the benefits conferred by current evidences , emphasis has been placed on potential therapeutic effects related to active contraction of paralyzed muscles improving muscular and skeletal metabolism , cardiopulmonary condition , and general improvement of physiological and psychological performance, including partial recovery of leg function in incomplete SCI subjects .…”
mentioning
confidence: 99%
“…There were 12 studies for qualitative synthesis, such as one RCT study and 11 non-RCT studies. Eight of them were quantitatively analyzed for meta-analysis (Sköld et al, 2002;Krause et al, 2008;Szecsi and Schiller, 2009;Mazzoleni et al, 2013Mazzoleni et al, , 2017Ralston et al, 2013;Kuhn et al, 2014;Yas ˛ar et al, 2015), and four studies were excluded due to reasons, such as case report (n = 1) (Fattal et al, 2018), no MAS result of post-test (n = 2) (Reichenfelser et al, 2012;Popovic-Maneski et al, 2018), and only LEMS data included (n = 1) (Sadowsky et al, 2013). The flowchart is shown as Figure 1.…”
Section: Studies Includedmentioning
confidence: 99%
“…However, Arnold et al (1992) found that FES-cycling training 30 min per session for 3 months improved cardiovascular fitness and thigh girths, but spasticity became intense in the individuals with SCI. Some studies showed no effect of FES-cycling training on spasticity in the patients with SCI (Sköld et al, 2002;Mazzoleni et al, 2013;Ralston et al, 2013). These controversial findings may be due to small sample sizes, heterogeneity of the studied populations, different training protocols, and the different assessment tools used.…”
Section: Introductionmentioning
confidence: 99%